The study of SMM as a virus strategy in the media space - V L Mouzykant (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2014)
The article describes the phenomenon of social marketing in the Internet that has changed the idea of the relationships between the addresser and the addressee in the social networks. The author analyzes the typology, genesis and consequences of the virus marketing in social networks from the perspective of the sociological analysis of media. The article considers the influence of the Internet on the behavior of the Russians, the methods of measuring the impact of the emerging new media. The author identifies different strategies in the SMM-market, such as creative content, digital-projects, media planning, simple content, government, close-to-government and educational projects. ROMIR within the GemuisAudience project conducted a research among 20 thousand Russian respondents to monitor their behavior in the sphere with the help of special sensors that identify Internet preferences of the Russians. The first results of the project revealed a trend - the more interesting the content the more likely the user is to share the app with his friends.